Comparative Evaluation of Cyclic Fatigue Resistance of Two Single-file Rotary Instruments in Simulated Stainless Steel Curved Canals - M Sedigh-shams; R Ebrahimi; B Asheghi; F Eskandari (Islamic Azad University, 2022)
Background and Aim: Despite the advantages and conveniences that NiTi files offer, their main drawback is their catastrophic fracture due to cyclic and torsional fatigue leading to instrument separation. This study aimed to compare the cyclic fatigue resistance of two single file engine-driven instruments, HyFlex EDM and NeoNiTi A1, in simulated curved canals. Materials and Methods: In this experimental study, NiTi endodontic instruments with a similar tip size of 0.25 mm were investigated in two groups of 20: HyFlex EDM (group A) and Neoniti A1 (group B). Evaluation of cyclic fatigue was conducted in a stainless steel artificial canal with a 60° angle and 5-mm radius curvature. HyFlex EDM and Neoniti A1 instruments were operated based on the instruction for use provided by the manufacturers. All instruments were rotated (at 400 rpm) until fracture, and the number of cycles to fracture (NCF) and the length of the fractured tip were documented. Means and standard deviations of NCF and fragment length were determined for each system and compared using the Mann-Whitney test (P<0.05). Results: A statistically significant difference was detected when comparing the NCF, and time until fracture of HyFlex EDM and Neoniti A1 instruments (P=0.001). HyFlex EDM instruments showed significantly greater mean NCF in comparison with Neoniti A1 instruments (2984.75 ± 576.14 vs. 839.55 ± 305.5 NCF). No statistically significant difference was found in the mean length of the fractured fragments between the instruments (P=0.683). Conclusion: HyFlex EDM instruments showed significantly greater cyclic fatigue resistance compared with Neoniti A1 instruments.